2020
DOI: 10.1063/1.5139889
|View full text |Cite
|
Sign up to set email alerts
|

Seed-packed dielectric barrier device for plasma agriculture: Understanding its electrical properties through an equivalent electrical model

Abstract: Seeds have been packed in a dielectric barrier device where cold atmospheric plasma has been generated to improve their germinative properties. A special attention has been paid on understanding the resulting plasma electrical properties through an equivalent electrical model whose experimental validity has been demonstrated here. In this model, the interelectrode gap is subdivided into 4 types of elementary domains, according to whether they contain electric charges (or not) and according to their type of med… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
0
7
1
Order By: Relevance
“…Considering that the average volume of a lentil seed is 23.84 mm 3 and that 100 of them are introduced in Vreactor (6  15  65 mm 3 ), the occupancy rate is estimated at 40.7%. This value is significantly lower than the one calculated in our previous work where a value as high as 0.67 = 67 % is found because of the larger dimensions of the reactor (30 cm 3 ) [34].…”
Section: Table 2 Key Numbers Relating To the Seed-to-seed (As/s) And ...contrasting
confidence: 80%
See 1 more Smart Citation
“…Considering that the average volume of a lentil seed is 23.84 mm 3 and that 100 of them are introduced in Vreactor (6  15  65 mm 3 ), the occupancy rate is estimated at 40.7%. This value is significantly lower than the one calculated in our previous work where a value as high as 0.67 = 67 % is found because of the larger dimensions of the reactor (30 cm 3 ) [34].…”
Section: Table 2 Key Numbers Relating To the Seed-to-seed (As/s) And ...contrasting
confidence: 80%
“…If the absence/ presence of seeds does not significantly change the profile of V pl , a strong effect is observed on the peaks of current: their magnitude appears roughly twice lower if seeds are introduced in the plasma reactor. From an 'equivalent electrical circuit' point of view, the stack of seeds corresponds to a resistor in parallel with a capacitor [31]. Its resistance value is so high that the electric charges passing from the electrode to the counterelectrode are never transferred through this stack; they are only transferred by the plasma, through the interstices.…”
Section: Characterization Of the Seed-stacked Dielectric Barrier Devicementioning
confidence: 99%
“…In the case of treatment with an argon plasma jet, germination was already 100% in untreated seeds [17]. In another treatment with an IC RF air plasma [16], as well as in a seed-packed DBD reactor with helium [18], germination of untreated seeds was also >90%, and the plasma treatment accelerated the germination in both cases. Germination percentage was increased by plasma treatment in other legume species such as lentil [15], mung bean [29], pea [21], and soybean [13].…”
Section: Germination Percentagementioning
confidence: 96%
“…At 5 min, the shortest treatment time in the oxygen DBD experiment, the treatment also increased hypocotyl and radicle length, but prolonged treatment inhibited germination [14]. One publication that primarily studied electrical properties in a seed-packed DBD device also found that compared to untreated seeds, plasma-treated bean seeds germinated quicker while the germination percentage remained unchanged for seeds treated for 2 min [18].…”
Section: Introductionmentioning
confidence: 99%
“…For example, when a DBD is powered at 8 kV (600 Hz) to process seeds, Judée and Dufour have shown that a batch of lentil, bean or corn seeds has a capacitance of around 20 pF, which translates into a plasma power of 1350 mW. In contrast, a batch of radish, coriander or sunflower seeds has a capacitance of 14 pF, resulting in a plasma power of 1200 mW [20]. The shape of the seeds can also affect the discharge properties since it determines both the contact areas between seeds as well as the tridimensional spaces (interstices) between them where microdischarges occur.…”
Section: Influence Of Seeds On Plasmamentioning
confidence: 99%